Assistant Writer in Examinations: Lived Experiences of Students with Deafblindness (NPRC Journal of Multidisciplinary Research, 2025)
Background: Students with deafblindness face significant educational challenges, including a lack of accessible learning materials and discriminatory assessment practices. These barriers prevent them from fully exercising their educational rights, revealing a gap between inclusive education policies and their practical implementation. Despite constitutional mandates and international agreements advocating for inclusive education, marginalized students with disabilities continue to experience systemic neglect.Objective: This study aims to explore the lived experiences of students with deafblindness in educational settings, focusing on the challenges they face in accessing learning materials, participating in assessments, and receiving institutional support.Methods: A phenomenological research approach was used to capture the firsthand experiences of students with deafblindness. Data was collected through semi-structured interviews with three participants, allowing for an in-depth understanding of their educational struggles and the systemic barriers they encounter.Findings: The study reveals that students with deafblindness frequently experience marginalization due to inadequate support for braille literacy from government officials. Additionally, the lack of accessible assessment accommodations places an undue burden on these students, further limiting their educational opportunities. Participants stressed the need for government institutions to take active measures to fulfill constitutional and international commitments to inclusive education.Conclusion: The findings highlight the urgent need for systemic reforms to ensure that inclusive education policies translate into meaningful support for students with deafblindness. Strengthening accessibility measures, improving braille literacy support, and adapting assessment practices are essential steps toward reducing educational disparities.Novelty: This study provides a critical examination of the disconnection between inclusive education policies and their real-world implementation, emphasizing the specific struggles of students with deafblindness. By centering their lived experiences, the research offers valuable insights into the urgent reforms needed to create a truly inclusive educational system.